Effect of unripe berline banana flour on synbiotics yogurt of physicochemical and microbiological properties - Agustin, Firda; Putri, Ratih; Febriyatna, Ayu (Alma Ata University Press, 2025)
Background: Synbiotic yogurt is a fermented milk product that combines probiotic bacteria with ingredients that contain prebiotic components. Unripe berlin banana flour contains resistant starch that can act as a prebiotic.Objectives: This study aimed to determine the effect of the addition of unripe banana flour to synbiotic yogurt on physicochemical and microbiological properties. Methods: This research is true experimental with a completely randomized design. The treatment group consisted of 4 groups, namely P0 (2% inulin), P1 (1% UBF), P2 (2% UBF), and P3 (3% UBF). The process of making unripe berlin banana flour synbiotic yogurt begins with making berlin banana flour, yogurt starter, and synbiotic yogurt. The tests conducted were physicochemical and microbiological. Physicochemical test data was analyzed descriptively and microbiological tests were used the Kruskall walls test, with 95% level confidence using SPSS.Results: In the physicochemical test, it was found that the group with the addition of UBF (P1, P2, P3) had higher ash content, energy, resistant starch, and viscosity than the inulin group (P0). In the microbiological test, it was found that there were significant differences BAL total between treatment groups (P=0.002), there were no differences related to coliform parameters between groups (P=0.707), and salmonella was identified as negative in all groups.Conclusions: The addition of unripe berlin banana flour can affect the LAB content of yoghurt and has the potential to be a functional food product with health benefits.